PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI TERHADAP KINERJA GURU DIMEDIASI KOMITMEN ORGANISASI ( Studi Pada Guru Sekolah Dasar Negeri di UPT. Dinas Pendidikan Kecamatan Tlogowungu Kabupaten Pati ) - Wiwik Sugiyarti, 11.52.02.0035 (Students Journal of Economic and Management, 2013)
The purpose of this study to examine and analyze the effect of principalâs leadership and motivation on teacher performance mediated organizational commitment. The object of research is a public primary school teachers in the District Education Tlogowungu Pati. The number of samples in this study is 111 respondents. The sampling technique used purposive sampling method.Technical test data used in this study include validity, reliability test, the classic assumption test, multiple regression analysis, model test, t test and a test of mediation to test and prove the research hypothesis. KMO value of all variables in this study showed greater than 0.50 and the Cronbach alpha values above 0.6, which means the adequacy of the sample met ( valid ) and reliable. The results of the analysis and discussion showed that the principals leadership has positive and significant impact on organizational commitment; motivation has positive and significant impact on organizational commitment; leadership principalâs have a positive and significant impact on teacher performance; motivation has positive and significant impact on teacher performance; commitment influential organizations positive and significant impact on teacher performance. Organizational commitment is not able to mediate the influence of either the principals leadership and motivation on the performance of public primary school teachers in District Education Tlogowungu Pati. Keywords: Principals Leadership, Motivation, Organizational Commitment and Performance